THE ROLE OF EDUCATION IN THE FORMATION OF KNOWLEDGE SOCIETY - Jasarat Fikret Valehov (Russian State Vocational Pedagogical University, 2016)
The article aims to define opportunities of education in the formation of knowledge society, which is an integral part of information society and closely related to such an important determinant of the level of society's development as social capital. Methods. Methodological basis for analyzing this problem lies in a systematic approach to studying social processes, while a monographic method in methodology. Based on this method, the author tried to define the philosophic mission of educational institutions, which they had performed before the emergence of knowledge economy. This was a significant foundation for further development of society. Results. In the age of knowledge economy international competition is based on search for talents. The author defined that in knowledge society students receive necessary knowledge, which gives them an advantage over others. University education is the focus of attention on a global scale. Ensuring prosperity and well-being of society requires better use of human mind. Scientific novelty of the article concludes in well-founded proof that countries where education is built at an academic level can ensure the formation of a new, promising generation and can withstand international competition. Practical significance lies in the conclusion that the system of vocational education should cover all spheres of economy, science and culture meeting the needs and interests of the country.